Liquid-Metal-Assisted Synthesis of Single-Crystalline TiC Nanocubes with Exposed {100} Facets for Enhanced Electrocatalytic Activity in the Hydrogen Evolution Reaction - Jeong, Kyoung-Jin; Lee, Yohan; Huynh, Thanh-Nam; Nersisyan, Hayk; Suh, Hoyoung; Lee, JongHyeon (WILEY-V C H VERLAG GMBH, 2023)
Although TiC nanostructures show promise as non-noble-metal-based electrocatalysts, improved synthesis methods are required. Herein, single-crystalline TiC nanocubes with exposed {100} facets are grown by combusting TiO2 + kMg + C reactive mixtures (k = 4-6.5 mol) in argon. During the synthesis, the temperature increases to 1200-1550 degrees C and excess Mg (2-4.5 mol) forms a liquid pool. The obtained TiC nanocubes have edge lengths of 50-300 nm and surface areas of 12.2-30.05 m(2) g(-1). Insights into the TiC nanocube formation mechanism are obtained using density functional theory modeling of the surface energies of TiC nanocrystals and shape visualization using the Wulff construction method. During TiC nucleation and growth within the Mg melt, liquid Mg likely acts as a capping agent for {111} facets, thus promoting the formation of {100} facets. The TiC nanocubes show high electrocatalytic activity for the hydrogen evolution reaction, with a lower overpotential (0.298 V at 10 mA cm(-2)) than other TiC nanostructures (0.400-0.815 V).